Deciphering The Prominent Security Tools Ofkali Linux (International Journal of Engineering and Computer Science, 2015)
Kali Linux is the operating system that is reverenced by almost every cyber security professional since 2013.While Kali is extensivelydeveloped for penetration testing and digital forensics, it is considered as quintessential operating system for tenderfoot hackers.Basically Kali is the renaissance of Backtrack which typically means that kali is the offspring of backtrack.When it comes to security Kali has the eminent set of exemplary tools. These tools are panacea for your own security practices before a real intruder does it.Among all such tools,there are tools which are highly enamored by security research professionals. This paper enumerates these top tensecurity tools of Kali Linux and is an epistle that will hanker the sinister powers for the use of good.